PEMANFAATAN SISTEM INFORMASI JASA PERCETAKAN E-COMMERCE CV. SPORTA JAWARA INDONESIA - Alfred Putra; Kartono Kartono; Jacki Jacki (INTEKSIS, 2022)
This research was conducted at CV. Sporta Jawara Indonesia because of the CV system. Sporta Jawara Indonesia is still recording manually, which has led to a search for data on ordering printing services. To solve this problem, CV. Sporta Jawara Indonesia needs a system that can manage data and information in printing services. The form of research and data methods used were interviews, literature study, and observation. The diagram used is the Unified Modeling Language (UML), while the information system design application is the Web programming language with the help of the Adobe XD application used to design the web in images, Adobe Dreamweaver and Sublime for easier coding, MySQL as a database, Xampp connector and managed PhpMyadmin. Based on research conducted at CV. Sporta Jawara Indonesia can be seen that the system is running now on CV. Sporta Jawara Indonesia still uses a manual recording system, therefore it must be done a new system design using a web-based system to help CV. Sporta Jawara Indonesia improves performance through this system which can store and process CV data. Sporta Jawara Indonesia is a company report that is used as information for companies in making decisions. The conclusion obtained from the design of a web-based online printing service information system on CV. Sporta Jawara Indonesia is the proposed system for CV. Sporta Jawara Indonesia and is expected to be able to assist companies in carrying out the ordering process and ordering data ordering. Suggestions for the CV. Sporta Jawara Indonesia is to be able to maximize the system properly and always back up data periodically to avoid data loss. Keywords: Design, Systems, Information, Printing